2018
DOI: 10.1111/joop.12245
|View full text |Cite
|
Sign up to set email alerts
|

Leader–member exchange social comparisons and follower outcomes: The roles of felt obligation and psychological entitlement

Abstract: In the current study, we aimed to extend the understanding of how and when leader–member exchange social comparison (LMXSC) influences followers’ work behaviour. Based on social exchange theory, we argue that felt obligation to one's leader is a mediator of the relationship between LMXSC and follower outcomes. Further, we posit that the relationship between LMXSC and felt obligation will occur over and above overall LMX quality. We also investigate whether the effect of LMXSC is not consistent across employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 57 publications
(105 reference statements)
2
49
0
Order By: Relevance
“…This indicates that narcissism is a particular type of trait making it likely to respond differently to economic LMX relationships than the normal pattern that is often observed. In a related vein, Lee et al (2019) found that, depending on followers' level of psychological entitlement, he or she would value reciprocity of social exchanges differently (Lee et al, 2019). Arguably, such findings indicate that depending on an individual's level of narcissism or other dark traits may make them respond differently or even positively to an economic LMX relationship as it may serve their expectations and worldview.…”
Section: Follower Characteristics and Follower Lmxmentioning
confidence: 98%
“…This indicates that narcissism is a particular type of trait making it likely to respond differently to economic LMX relationships than the normal pattern that is often observed. In a related vein, Lee et al (2019) found that, depending on followers' level of psychological entitlement, he or she would value reciprocity of social exchanges differently (Lee et al, 2019). Arguably, such findings indicate that depending on an individual's level of narcissism or other dark traits may make them respond differently or even positively to an economic LMX relationship as it may serve their expectations and worldview.…”
Section: Follower Characteristics and Follower Lmxmentioning
confidence: 98%
“…We followed the recent studies (e.g., see Eissa and Lester, 2017 ; Hongbo et al, 2019 ; Lee et al, 2019 ) to conduct data analysis through SPSS PROCESS macro developed by Preacher et al (2007) . Our study developed formal mediation and moderated mediation (two-way interaction) hypotheses, so we performed a series of analyses described by Preacher et al (2007) .…”
Section: Methodsmentioning
confidence: 99%
“…Social exchange theory emphasizes that individual exchanges do not produce invariant reciprocity because individuals can vary in valuing the rule of reciprocity (Cropanzano and Mitchell, 2005;Love and Forret, 2008;Lee et al, 2019a). Whether or not a high-quality LMX promotes newcomer performance depends on the newcomers' perspective on this relationship and the value they place on the rule of reciprocity.…”
Section: Moderator: Psychological Entitlementmentioning
confidence: 99%
“…Scholars have increasingly adopted a SET ( Blau, 1964 ) lens to understand how interpersonal exchange relationships in work settings influence workplace behavior (e.g., Lee et al, 2019a ). SET is built on the principle of reciprocity ( Gouldner, 1960 ) and posits that individuals will feel compelled to reciprocate a positive exchange from another individual.…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation